Role of structural change and competitiveness on productivity in ASEAN-5 - Munusamy, Subramaniam (2015)
This study intends to investigate the dynamic role of structural change and competitiveness on the labor productivity of ASEAN-5, namely Indonesia, Malaysia, Philippines, Singapore and Thailand. Using the well-known shift-share analysis of panel data between 1975 and 2005, this study found a strong presence of structural bonus hypothesis in the services sector. Thus, it confirms the ability of ASEAN-5 to reallocate labor resources from low to high productive sectors which resulted in the aggregate productivity growth of the services sector. However, the prevalence of Boumol’s structural burden implied that the structural change has implicated negative effect on the aggregate growth of industry in the most of ASEAN-5 countries except for Thailand. Besides shifting labor force away from progressive sectors towards ‘stagnated’ sectors with low productivity growth, structural change appears to weaken the aggregate growth of labor productivity in the industry. In the long run, it increases the chances of labor force to get ‘trapped’ in the stagnant industries and tend to diminish income per capita growth. Moreover, regression analysis from 2006 to 2012 founds a robust relationship between labor productivity growth and competitiveness that largely rest in the foreign market capitalization. Equally, private spending on R&D as well as FDI and technology transfer played a major role in raising labor productivity level within the ASEAN-5. This study, therefore, proposes country-specific institutional policies that emphasize in a stable macroeconomic environment, comprehensive assessment of partial industrialization conditions and government intervention in the facilitation of free trade and Research and Development (R&D) are essential the key determinant factors in salient structural change and compete in ASEAN-5.